Membrane Adsorption Enhances Translocation of Antimicrobial Peptide Buforin 2 - Khodam Hazrati, Mehrnoosh; Vácha, Robert (The journal of physical chemistry. B, 2024)
Despite ongoing research on antimicrobial peptides (AMPs) and cell-penetrating peptides (CPPs), their precise translocation mechanism remains elusive. This includes Buforin 2 (BF2), a well-known AMP, for which spontaneous translocation across the membrane has been proposed but a high barrier has been calculated. Here, we used computer simulations to investigate the effect of a nonequilibrium situation where the peptides are adsorbed on one side of the lipid bilayer, mimicking experimental conditions. We demonstrated that the asymmetric membrane adsorption of BF2 enhances its translocation across the lipid bilayer by lowering the energy barrier by tens of kJ mol-1. We showed that asymmetric membrane adsorption also reduced the free energy barrier of lipid flip-flop but remained unlikely even at BF2 surface saturation. These results provide insight into the driving forces behind membrane translocation of cell-penetrating peptides in nonequilibrium conditions, mimicking experiments.
Keywords: Molecular Dynamics Simulation; Lipid Bilayers; Antimicrobial Peptides; lipidové dvojvrstvy; terpeny; Cell-Penetrating Peptides; Adsorption; kationické antimikrobiální peptidy; Terpenes; simulace molekulární dynamiky; antimikrobiální peptidy; Proteins; proteiny; Thermodynamics; Antimicrobial Cationic Peptides; penetrační peptidy; termodynamika; buněčná membrána; adsorpce; Cell Membrane